(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The growing clinical adoption of fixed-dose combinations (FDCs) containing sodium-glucose cotransporter-2 (SGLT-2) inhibitors, dipeptidyl peptidase-4 (DPP-4) inhibitors, and metformin hydrochloride for type 2 diabetes mellitus has outpaced the development of validated, sustainable analytical methods for their simultaneous quantification. Objective: This review consolidates Analytical Quality by Design (AQbD)-based reversed-phase high-performance liquid chromatography (RP-HPLC) approaches developed for antidiabetic FDCs and benchmarks their environmental sustainability across multiple greenness assessment tools. Methods: Reported AQbD-driven RP-HPLC methods for antidiabetic FDCs were reviewed within the framework of ICH Q8(R2), Q9(R1), and Q14. Risk-assessment tools (Ishikawa diagrams, Failure Mode and Effects Analysis) and Design of Experiments strategies (Plackett-Burman screening, Box-Behnken, and Central Composite Designs) were evaluated for their contribution to method optimization and robustness. Method greenness was comparatively assessed using eight tools: NEMI, Analytical Eco-Scale, GAPI, Modified/Complex GAPI, AGREE, AGREEprep, BAGI, and the Analytical Method Greenness Score (AMGS). Results: Comparative benchmarking revealed substantial divergence among greenness tools when scoring identical reported methods, indicating that single-metric sustainability claims are insufficient for regulatory-ready validation. AQbD-integrated DoE strategies consistently outperformed conventional one-factor-at-a-time optimization in robustness for multi-component FDCs with heterogeneous physicochemical properties. Conclusion: A decision framework is proposed for selecting greenness metrics and DoE designs based on FDC composition, guiding method developers toward stability-indicating RP-HPLC methods that satisfy both ICH Q2(R2) validation requirements and environmental sustainability goals.